2019
DOI: 10.1111/apa.14975
|View full text |Cite
|
Sign up to set email alerts
|

Delivery room skin‐to‐skin contact for preterm infants—A randomized clinical trial

Abstract: Aim To investigate the effects of 60 minutes delivery room skin‐to‐skin contact (DR‐SSC) compared with 5 minutes visual contact (VC) on mother‐child interaction (MCI), salivary cortisol, maternal depression, stress and bonding at 6 months corrected age. Methods A single‐centre randomized controlled trial conducted in a German level III NICU. Eighty‐eight preterm infants (25‐32 weeks of gestational age) were randomized after initial stabilization to either 60 minutes DR‐SSC or 5 minutes VC. Forty‐five infants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 36 publications
(70 reference statements)
3
87
0
4
Order By: Relevance
“…Additionally, he utility of multimodal monitoring over the use of physiological monitoring for the prediction of IVH warrants further investigation. Furthermore, the specific impact of multimodal monitoring on opportunities for mother-baby interaction and the establishment of parental ties will need investigation in future studies [22, 23]. In the future, advanced systems using wireless monitoring technology may help alleviate parental anxiety and allow for practices such as skin-to-skin contact during multimodal monitoring [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, he utility of multimodal monitoring over the use of physiological monitoring for the prediction of IVH warrants further investigation. Furthermore, the specific impact of multimodal monitoring on opportunities for mother-baby interaction and the establishment of parental ties will need investigation in future studies [22, 23]. In the future, advanced systems using wireless monitoring technology may help alleviate parental anxiety and allow for practices such as skin-to-skin contact during multimodal monitoring [24, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of mother-child interaction responses (primary outcome) at 6 months corrected age was better (p = 0.04) in those who received direct early skinto-skin contact. NICU admission temperature was higher in the early skin-to-skin contact group (median: 36.6°C vs. 36.1°C,p < 0.001).The authors concluded that delivery room skin-skin contact promotes maternal-child interaction, decreases maternal depression and bonding problems, and may benefit preterm development 16. In our experience, mothers invariably want to cuddle their extremely preterm newborns.…”
mentioning
confidence: 70%
“…NICU admission temperature was higher in the early skin‐to‐skin contact group (median: 36.6°C vs. 36.1°C, p < 0.001). The authors concluded that delivery room skin–skin contact promotes maternal‐child interaction, decreases maternal depression and bonding problems, and may benefit preterm development 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the incidence of PPD among these mothers was very high (36.6%). Many randomized controlled trials have implicated that insufficient contact with babies will increase the odds of PPD [30][31][32]. Therefore, clinical healthcare workers should provide psychological supplies to mothers with NICU babies.…”
Section: Discussionmentioning
confidence: 99%